All-fiber low threshold tunable multimode Q-switched mode locked fiber laser using a few mode Er-doped fiber. (1st May 2023) - Fan, Yunlong; Zhang, Peng; Ning, Yuzhu; Liu, Yang; Wei, Jia; Tong, Shoufeng
Abstract: We report an all-fiber low threshold (70 mW) multimode Q-switched mode-locked (QML) fiber laser at 1.5 μ m. Nonlinear polarization rotation and a few mode Er-doped fiber (FM-EDF) were both adopted to achieve a low threshold QML operation initially, and the later experimental results showed and verified that the FM-EDF was the key factor of the QML pulses generation. A multimode QML state at 70 mW pump power was obtained with an 18 μ s Q-switched pulse width and a 7.41 kHz repetition rate. The repetition rate and pulse width of the mode-locked pulses within the Q-switched envelope were 16.9 MHz and ∼910 ps respectively. The multimode QML fiber laser can be turned from 1561.8 nm to 1575.1 nm owing to the multimode interference and the fiber birefringence filtering effect. The QML pulses with dual-wavelength and three-wavelength were also observed by manipulating the polarization controllers and increasing the pump power. The experimental results showed that multimode QML pulses can be achieved with a short FM-EDF at a lower pump power in an all-fiber multimode cavity. The generated low threshold and tunable QML multimode fiber laser has potential application in measuring and mode-division multiplexed system.